Maternal Factors Associated with Early Neonatal Sepsis: A Multicenter Cross-Sectional Study - Madiha Iqbal, Zia Muhammad, Ibrahim Bin Afsar Jan, Naheed Akhtar, (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Early neonatal sepsis is a dangerous medical condition that affects children under 28 days of age. There are many maternal risk factors that lead to early onset of neonatal sepsis. Objective: The aim of this study was to find out the maternal factors associated with early neonatal sepsis. Materials and method: The present multicenter cross-sectional study was conducted at the department of Gynae Hayatabad Medical Complex Peshawar and Paediatric Department Khyber Teaching Hospital Peshawar from January 2022 to June 2022 after taking approval from the ethical committee of the institute. The non-probability sampling procedure was applied for sample collection. The sample size was 260 individuals determined through WHO calculator. Neonates of both genders and different age groups (ranged 1-3 days) diagnosed with early neonatal sepsis were included. Data including name, age, residence, and contact details of each participant were recorded. Preterm birth, meconium-stained liquor, and PROM were noted as maternal risk factors (per operational definition). A statistical analysis of the collected data was done using SPSS version 20. Results: A total of 260 neonates diagnosed with early onset of sepsis were included in this study out of which male were 125(48.0%) and females were 135(51.9%). The mean age of the study population was 2.15+0.58 days. Majority of the neonates were in the age group 1-2 days 167 (64.2%) followed by age group 3 days 93(35.7%) respectively. The most prevalent maternal risk factors in the early neonatal sepsis was PROM 170 (65.3%) followed by meconium-stained fluid 80 (30.7%) and preterm birth 55 (19.6%) respectively. For maternal and gestational age and gender of the participants the data was stratified. Chi square test was used for stratification data and p-value <0.05 was considered statistically significant. Conclusion: Our study concluded that the major risk factor for early neonatal sepsis is prolonged rupture of membrane followed by meconium stained liquor and preterm delivery. Keywords: Neonatal sepsis, risk factors; prolonged rupture of membrane